Juridical Analysis on Crypto Assets: A Study of Collateral Institutions in the Indonesian Context - Tunggaesti, Dea; Anggriani, Jum; Wahyu, Andrey Mario (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to analyze crypto assets in the global aspects that have developed very rapidly, and the economic value of some cryptos has been widely recognized and factual at present; furthermore, with its value, it is treated as a virtual asset. As an asset, crypto may face the possibility of potential utilization as collateral in society and raises the issue of whether regulations and laws provide adequate regulation and protection against such utilization. This legal research aims at the development of law in such context which is considered crucial to provide legal protection for the public from opaque practices related to crypto and its risks that may affect the legal and economic interests of the parties concerned within the Indonesian jurisdiction. The method used is normative legal analysis with a statutory approach and secondary data sources, particularly literature review, Indonesian laws and regulations have been used in this research. The main result of this research is that the legal norms in Indonesian security law and the parties' freedom of contract may generally cover the utilization of assets of a legal entity as collateral, but it lacks legal norms and functions to protect the rights and economic interests of creditors against the potential risks of crypto assets, which may lead to unclear practices in society. Therefore, the need for legal development regarding security law in Indonesia needs to include and determine when crypto assets can or cannot be utilized as legal collateral in Indonesia's future, as well as legal functions and remedies to support the protection and legal certainty of current issues related to crypto asset risks.